Molecular medical parasitology - Marr, J. Joseph; Nilsen, Timothy W.; Komuniecki, Richard (Academic Press, 2003)
Contents include: -- -RNA editing and processing -- -Genomics -- -Post-transcriptional gene regulation -- -Genetic approaches to analysis of virulence -- -Protozoa and Helminth energy metabolism -- -Trypanosomatid surface carbohydrates -- -Plastids, mitochondria and hydrogenosomes -- -Neurotransmitters -- -Drug resistance in parasites -- -Medical implications of molecular parasitology